Duplication and maintenance of the Myb genes of vertebrate animals - Davidson, Colin J. (The Company of Biologists, 2012)
Gene duplication is an important means of generating new genes. The major mechanisms by which duplicated genes are preserved in the face of purifying selection are thought to be neofunctionalization, subfunctionalization, and increased gene dosage. However, very few duplicated gene families in vertebrate species have been analyzed by functional tests in vivo. We have therefore examined the three vertebrate Myb genes (c-Myb, A-Myb, and B-Myb) by cytogenetic map analysis, by sequence analysis, and by ectopic expression in Drosophila. We provide evidence that the vertebrate Myb genes arose by two rounds of regional genomic duplication. We found that ubiquitous expression of c-Myb and A-Myb, but not of B-Myb or Drosophila Myb, was lethal in Drosophila. Expression of any of these genes during early larval eye development was well tolerated. However, expression of c-Myb and A-Myb, but not of B-Myb or Drosophila Myb, during late larval eye development caused drastic alterations in adult eye morphology. Mosaic analysis implied that this eye phenotype was cell-autonomous. Interestingly, some of the eye phenotypes caused by the retroviral v-Myb oncogene and the normal c-Myb proto-oncogene from which v-Myb arose were quite distinct. Finally, we found that post-translational modifications of c-Myb by the GSK-3 protein kinase and by the Ubc9 SUMO-conjugating enzyme that normally occur in vertebrate cells can modify the eye phenotype caused by c-Myb in Drosophila. These results support a model in which the three Myb genes of vertebrates arose by two sequential duplications. The first duplication was followed by a subfunctionalization of gene expression, then neofunctionalization of protein function to yield a c/A-Myb progenitor. The duplication of this progenitor was followed by subfunctionalization of gene expression to give rise to tissue-specific c-Myb and A-Myb genes.